The Role of Brand Image in Mediating the Effects of Price and Product Quality on Purchase Decisions - Yolla Quaisyah Nias; Misbak Misbak; Keke Shabrina Nurmalitasari (Greenation Research & Yayasan Global Resarch National, 2026)
This study was conducted based on the increasing competition in the motorcycle industry, where companies are required to understand factors influencing consumer purchase decisions. The research object is consumers of Honda motorcycles at Alseda Motor Dealer, Indramayu. This study aims to analyze the effect of price and product quality on purchase decisions, with brand image as a mediating variable. A quantitative research method was applied using a survey approach. Data were collected from 100 respondents through questionnaires and analyzed using the Structural Equation Modeling approach with Partial Least Squares. The results show that price, product quality, and brand image have a positive and significant effect on purchase decisions. Furthermore, brand image significantly mediates the influence of price and product quality on purchase decisions. These findings indicate that competitive pricing and high product quality can strengthen brand image, which in turn enhances consumer purchase decisions. The study concludes that brand image plays an important strategic role in strengthening the impact of marketing factors on consumer decision-making and can be used as a reference for developing more effective marketing strategies.